RISK MANAGEMENT IN THE IMPLEMENTATION OF PUBLIC-PRIVATE PARTNERSHIP INFRASTRUCTURE PROJECTS - DIACHEK, Vitalii; MIROSHNICHENKO, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article highlights the theoretical and practical aspects of risk management in the implementation of public-private partnership (PPP) projects. The essence of risks in the context of PPPs, their types and sources of occurrence are investigated. The focus is on identifying, assessing and allocating risks between partnership participants, taking into account their resources, competencies and roles in the project.The key methods of risk management are considered: avoidance, minimisation, transfer and acceptance. The features of the use of management tools, such as insurance, financial guarantees, hedging, reserve funds, and contractual mechanisms, are described. The advantages and disadvantages of each approach are analysed, depending on the specifics of the project, industry and regulatory environment.The article provides practical recommendations for improving the efficiency of the risk management process at all stages of the PPP project life cycle. The author emphasises the importance of preliminary risk analysis, development of detailed risk mitigation plans, as well as monitoring and adaptation of the management strategy during the project implementation.The author emphasises the importance of interaction between the public and private sectors in the context of risk allocation, in particular through the establishment of a clear legal framework, transparency of processes and ensuring the responsibility of the parties. The use of the proposed approaches will help to reduce the negative impact of risks on the effectiveness of PPP projects, optimise resources and achieve the goals of the partnership.The results of the study may be useful for representatives of government agencies, private business, investors and academics involved in the development, implementation and analysis of PPP projects.
Keywords: risk management; public-private partnership; risk allocation; risk minimisation; project efficiency